Urinary Complication Following Cystocele Repair in Pelvic Organ Prolapse - Shrestha, Sweety (Nepal Journal of Obstetrics and Gynaecology, 2017)
Aims: Pelvic organ prolapse is a common condition in our country which affects the quality of life of many women. After vaginal operations for genital prolapse, there is increased chance of urinary tract infections, retention of urine and re-catheterization.The objective of this study is to evaluate women with cystocele in terms of clinical profile, different modalities of treatment and the complication following repair. Methods: It is a descriptive study carried out amongst 80 cases of cystocele irrespective of associated uterine descent and stress incontinence of urine in College Of Medical Sciences – Teaching Hospital, Nepal from 1/9/201l to 30/10/2013. Results: During the study, 80 women with cystocele were enrolled. Majority of the women (66.3%, n =53) with cystocele were within 15 to 45 years and 53.8% (n=43) of them had parity beyond 5. Among these women, 51.4% (n=41) had second degree cystocele and 23.8% (n=19) had stress urinary incontinence. Majority of the women (58.8%, n=40) underwent vaginal hysterectomy with pelvic floor repair. Following surgery, the most common complication was urinary tract infection (14.7%, n = 10). Conclusions: In this study, majority of the cases with cystocele were in the reproductive age with parity beyond 5 while maximum number of the women with cystocele had associated third degree uterocervical descent. Urinary tract infection was the commonest complication following surgical treatment followed by retention of urine.